Integration degree between tourism industry and liquor culture industry: A case study of Maotai Town - ZHOU Jianhong, LI Huiyao (Zhongguo niangzao)
The development of liquor culture tourism has a positive effect on promoting rural revitalization. Based on the theory of industrial integration and using Herfindahl-type index (HI) to evaluate the degree of industrial integration between the liquor culture industry and tourism industry in Maotai Town. In addition, the mechanism of sustainable development of liquor culture tourism industry was further explored. The results showed that the market integration degree HI of Maotai tourism industry was 0.23, the product integration degree HI was 0.25, and the management integration degree HI was 0.34. According to the reverse indicator of the Herfindal index, the market integration degree was the lowest, the management integration degree was the highest, and the product integration degree was between the two. This indicated that Maotai Town attached great importance to the development of liquor culture tourism industry, but there was great space for improvement in the market and products.